(untitled) (Historia, 2021)
A survey of thoughts on the so-called "egodokument" as a source for historical research The Dutch term egodokument was coined approximately forty years ago to identify memoirs, autobiographies, diaries, travel journals, letters and interviews as a separate category of historical sources. It is claimed that the description fulfils a need that also exists in other languages and is not satisfactorily addressed by the English personal document, the French document personnel or the German Selbstzeugnis. Egodokumenten can be defined as documents in which the user is confronted by an "I" as writing and explaining subject. This survey assesses the significance of the egodokument for the historian, the motivation behind the content of such sources and the problems encountered in their classification and definition. An attempt is made to determine the extent to which their subjective nature might impinge upon their reliability as historical sources. It is concluded that there is no fundamental difference between egodokumenten and other historical texts in this respect : all have basically evolved from a narrative "I" - whether the author chooses to hide behind the information given, or reveals his or her identity in the text. Several approaches borrowed from the social sciences and literary theory are employed to extract maximum benefit from these self-centred egodokumenten. Finally, a strategy for the publication of egodokumenten is suggested and an indication is given of the possibilities for historians in the application of these sources. Die term egodokument is ongeveer veertig jaar gelede in Nederland gemunt om memoires, outobiografieë, dagboeke, reisverhale, briewe en onderhoude as aparte kategorie historiese bronne te beskryf. Daar word aangevoer dat dit aan 'n behoefte voldoen wat ook in ander tale bestaan en waarvoor die Engelse personal document, die Franse document personnel en die Duitse Selbstzeugnis geen volkome ekwivalent bied nie. Egodokumente kan omskryf word as dokumente "waarin de gebruiker zich gesteld ziet tegenover een 'ik' ... als schrijvend en beschrijvend subject. In hierdie ondersoek word besin oor die belang van egodokumente vir historici, die motiverings agter die totstandkoming daarvan en die probleme random die definiëring en klassifisering van bronne binne die kategorie "egodokument". Daar word gevra na die mate waarin die subjektiewe aard van egodokumente die betroubaarheid daarvan belemmer en tot die gevolgtrekking gekom dat egodokumente nie fundamenteel verskil van ander soorte bronne wat immers óók gekonstrueer is deur 'n vertellende, hetsy meer of minder verskuilde, "ek" nie. Van die benaderings wat uit die sosiale wetenskappe en die literatuurstudie geleen word om die hoë graad van "ek"-gerigtheid in egodokumente ten beste te benut, word genoem. Ten slotte word begin oor publikasiestrategieë vir egodokumente en die toepassingsmoontlikhede van hierdie tipe bronne vir historici.